Diagnostic accuracy of C-terminal fragment of type I procollagen in detection of hidden heart failure in hypertensive males - Kolesnyk M.Yu. (Medičnì Perspektivi)
Purpose: to estimate diagnostic accuracy of C-terminal fragment of type I procollagen (PICP) in hypertensive males with hidden chronic heart failure (CHF). The study included 220 men with uncomplicated arterial hypertension (mean age 52 (46-58) years). The control group consisted of 40 healthy men of similar age. Ambulatory blood pressure monitoring, transthoracic echocardiography and speckle tracking echocardiography was performed to all participants. All patients underwent treadmill test with post-exercise evaluation of left ventricular (LV) filling pressure by tissue Doppler Е/е' ratio to reveal hidden CHF. The post-exercise Е/е'≥13 was considered to be pathological. PICP levels in plasma were determined by ELISA. The PICP concentration was significantly higher in men with hypertension (132,3 (81,3-216,8) ng/ml) as compared with healthy subjects (93.2 (64,7-133) ng/ml) (p=0,0068). The presence of LV hypertrophy did not affect the level of PICP (p=0,58). 16 patients presented pathological result of diastolic stress test revealing signs of hidden heart failure. PICP concentration was 2-fold higher in these individuals as compared with other patients (p=0.01). The ROC-analysis revealed, that optimal cut-off point is 170.2 ng/ml for PICP to detect hidden CHF (area under curve – 0,68±0,08; 95% confidence interval – 0,61-0,74; sensitivity – 68,7%, specificity – 69,6%). The PICP level exceeding 170,2 ng/mL testifies to hidden CHF in hypertensive males.